Optimization of Xanthan Gum and Sorbitol Levels in the Mycophenolate Mofetil Powder for Oral Suspension - Amin Umrani; Homa Faghihi; Zohreh Mohammadi; Parastoo Mirzabeigi; Hamed Montazeri Ghods; Ali Rastegari (مجله دانشگاه علوم پزشکی گیلان)
Background Mycophenolate mofetil as an immunosuppressive agent is widely administered in patients with kidney disorders and following organ transplantation. The amounts of xanthan gum and sorbitol, as two excipients of mycophenolate mofetil, are influential on the final quality and stability of the suspension. Objective In this experimental study, we aim to optimize the levels of xanthan gum and sorbitol in the Mycophenolate mofetil powder. Methods A Central composite design was used to prepare the formulations. The amounts of xanthan gum and sorbitol were considered as independent variables while the sedimentation volume (F value) and concentration of active pharmaceutical ingredient (API) after preparation and after 3 months of storage at 45 ͦC were considered as dependent variables. The samples were prepared through wet granulation process. Chromatography analysis and determination of F value and API were then performed. Results Analysis of variance showed that the increase in the amounts of xanthan up to 75 mg provided higher F value and better protection of API after 3 months by 98%, while the increase of sorbitol from 10 to 25 g had no significant effect on these variables. Optimized sample composed of 16.69 g sorbitol and 68.81 mg xanthan gum. Predicted error was desirably less than 5%. Conclusion The proposed formulation of mycophenolate mofetil powder for oral suspension with optimum amounts of xanthan gum and sorbitol has good stability. High level of xanthan gum and moderate level of sorbitol are recommended for preparing an optimal product.